Diseño y fabricación de un prototipo de una prótesis para amputaciones de tipo transhumeral que facilite la natación - Basurto Chiriboga, Luis Josue (2024)
The aim of this research project is the design, simulation and construction of a prototype prosthesis designed to facilitate swimming in cases of transhumeral amputations. The first phase focused on the study of the various existing swimming strokes in order to select those to which it would be optimal to adapt the prosthesis. Then, a model of the user's amputated arm was obtained using the reverse engineering technique. Subsequently, the prototype was computationally modelled in order to carry out the relevant simulations. Once the simulations were completed, the prototype was built using additive manufacturing technology. This prototype consists of a paddle that is firmly attached to the grip handle, initially three prototypes are manufactured with specific adaptations to carry out tensile tests, following the guidelines of ISO 22523:2006:2006 (requirements and test methods for external limb prostheses and external orthoses), the tensile tests seek to measure the strength and durability of the prosthesis. This project focused on combining detailed research on swimming strokes, the application of reverse engineering and advanced simulations to design and build a swimming prosthesis specifically targeted at transhumeral amputees. The use of additive manufacturing ensures precision in the fabrication of the prototype, which includes a paddle solidly attached to the grip handle to optimize its performance in aquatic activities.